Risk Perceptions and Brand Extension Success: Just Another Antecedent or One that Shapes the Effects of Others? - Study of Examples in Textiles and Clothing - (:unkn) unknown (INST CHEMICAL FIBRES, 2014)
This research examines the role of risk perceptions on the success likelihood of brand extensions. Prior research has focused on two main factors as driving the brand extension success: brand loyalty and the perceived fit between the brand and extension product. However, the role of purchasing risk perceptions (physical, financial, psychological, etc.) in driving the brand extension success has not been discussed adequately in the literature. This study posits that (1) risk perceptions explain substantial incremental variance (in addition to those explained by brand loyalty and perceived fit of the extension) in consumers' willingness to purchase (WTP) measures and (2) risk perceptions also moderate the effects of brand loyalty and perceived fit on WTP These suggestions were tested separately for children's' products and parents' products. The results indicate that the effects of the perceived fit on WTP are higher in high risk situations than those in low risk situations only when parents purchase an extension product for the use of their children.
Keywords: risk perceptions; brand extension; brand loyalty; perceived fit; willingness to purchase; CONSUMER EVALUATIONS; DECISION-MAKING; PERCEIVED-RISK; FIT; INTENTIONS